Metal-Based Antibacterial and Antifungal Agents: Synthesis, Characterization, and In Vitro Biological Evaluation of Co(II), Cu(II), Ni(II), and Zn(II) Complexes with Amino Acid-Derived Compounds - Zahid H. Chohan; M. Arif; Muhammad A. Akhtar; Claudiu T. Supuran (Bioinorganic Chemistry and Applications)
A series of antibacterial and antifungal amino acid-derived compounds and their cobalt(II), copper(II), nickel(II), and zinc(II) metal complexes have been synthesized and characterized by their elemental analyses, molar conductances, magnetic moments, and IR, and electronic spectral measurements. Ligands (L1)–(L5) were derived by condensation of β-diketones with glycine, phenylalanine, valine, and histidine and act as bidentate towards metal ions (cobalt, copper, nickel, and zinc) via the azomethine-N and deprotonated-O of the respective amino acid. The stoichiometric reaction between the metal(II) ion and synthesized ligands in molar ratio of M: L (1: 1) resulted in the formation of the metal complexes of type [M(L)(H2O)4]Cl (where M = Co(II), Cu(II), and Zn(II)) and of M: L (1: 2) of type [M(L)2(H2O)2] (where M = Co(II), Cu(II), Ni(II), and Zn(II)). The magnetic moment data suggested for the complexes to have an octahedral geometry around the central metal atom. The electronic spectral data also supported the same octahedral geometry of the complexes. Elemental analyses and NMR spectral data of the ligands and their metal(II) complexes agree with their proposed structures. The synthesized ligands, along with their metal(II) complexes, were screened for their in vitro antibacterial activity against four Gram-negative (Escherichia coli, Shigella flexeneri, Pseudomonas aeruginosa, and Salmonella typhi) and two Gram-positive (Bacillus subtilis and Staphylococcus aureus) bacterial strains and for in vitro antifungal activity against Trichophyton longifusus, Candida albicans, Aspergillus flavus, Microsporum canis, Fusarium solani, and Candida glaberata. The results of these studies show the metal(II) complexes to be more antibacterial/antifungal against one or more species as compared to the uncomplexed ligands. The brine shrimp bioassay was also carried out to study their in vitro cytotoxic properties. Five compounds, (3), (7), (10), (11), and (22), displayed potent cytotoxic activity as LD50=8.974×10-4,7.022×10-4,8.839×10-4,7.133×10-4, and 9.725×10-4 M/mL, respectively, against Artemia salina.